1997
DOI: 10.1159/000244503
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Excretion of Endogenous Ouabain-Like Substance Is Reduced in NaCl Supplemented Premature Infants

Abstract: Ouabain or an isomer has been identified as endogenous ouabain-like substance (EOLS). The role of EOLS in the adaptation of premature infants to alterations of sodium balance was investigated by measuring urinary ouabain excretion serially in 9 low birth weight premature infants with (group S, mean birth weight 1,578 g, mean gestational age 30.4 weeks) and without (group NS, mean birth weight 1,537 g, mean gestational age 30.8 weeks) NaCl supplementation. The study was performed on the 7th day and weekly there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Thus it appears that in F344 ϫ NB rats, MBG is more responsive to a high NaCl intake, whereas OLC is more responsive to the isolation stress. Although in some previous reports OLC was shown to be responsive to high NaCl intake in normotensive rats (7,49), the results of other studies indicate that OLC is not stimulated by high NaCl or that it is responsive to high NaCl intake in animals that exhibit the salt-sensitive blood pressure increases (5,46,48). Thus Yamada and co-workers (48), using a highly specific ouabain antibody, demonstrated that although Wistar rats did not exhibit increases in plasma OLC levels during high NaCl intake, such increases did occur in NaCl-loaded Wistar rats after renal mass reduction.…”
Section: Discussionmentioning
confidence: 90%
“…Thus it appears that in F344 ϫ NB rats, MBG is more responsive to a high NaCl intake, whereas OLC is more responsive to the isolation stress. Although in some previous reports OLC was shown to be responsive to high NaCl intake in normotensive rats (7,49), the results of other studies indicate that OLC is not stimulated by high NaCl or that it is responsive to high NaCl intake in animals that exhibit the salt-sensitive blood pressure increases (5,46,48). Thus Yamada and co-workers (48), using a highly specific ouabain antibody, demonstrated that although Wistar rats did not exhibit increases in plasma OLC levels during high NaCl intake, such increases did occur in NaCl-loaded Wistar rats after renal mass reduction.…”
Section: Discussionmentioning
confidence: 90%
“…Ouabain like substance is also found in infants [132]. In the urine of premature infants supplemented with NaCl and in infants treated with furosemide, the level of ouabain excreted in the urine is reduced significantly [133,134]. Ouabain and ouabain-like substances are also found in the blood of hypertensive pregnant mothers and their infants [135][136][137].…”
Section: Oxidative Stress and Ouabain Levels Are Elevated In Infantsmentioning
confidence: 98%
“…It is tempting to postulate, therefore, that the activated renin-angiotensin II-AT1R pathway, either directly or indirectly via the generation of superoxide, enhances the redox-sensitive ADMA accumulation [163]. It is also to be considered that the production of the vasoactive adrenal steroid ouabain is also elevated, and its elevation proved to be dependent of the activity of the RAAS [164]. As ouabain has been suggested to mediate superoxide and peroxynitrite production, it may also contribute to endothelial dysfunction, and to the development of cardiovascular diseases later in life [165,166].…”
Section: Ras and Fetal Programmingmentioning
confidence: 99%